2019
DOI: 10.3390/w11050961
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan Alters Microbial Communities in Freshwater Microcosms

Abstract: The effect of triclosan on microbial communities that are found in soil and sediments is well documented. However, little is known regarding the possible effects of triclosan on microbial communities that are present in the column of freshwater streams as the antimicrobial is released from sediments or from water sewage outflow. We show that a concentration of triclosan as low as 1 ng/L decreases richness and evenness in freshwater microbial communities growing in the water column while using controlled experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Recent studies have demonstrated that TCS is an environmental stressor, alters the community structure and reduces species diversity and richness (Clarke et al, 2019;Oh et al, 2019;Peng et al, 2019). The simultaneous treatment with the three PPCPs gave alpha diversity values generally lower than those obtained for IBP and DCF, and higher than for TCS alone, but not significantly different from the controls, except for a higher evenness after 7 days.…”
Section: Bacterial Richness and Diversity In The Bps Microcosmsmentioning
confidence: 82%
“…Recent studies have demonstrated that TCS is an environmental stressor, alters the community structure and reduces species diversity and richness (Clarke et al, 2019;Oh et al, 2019;Peng et al, 2019). The simultaneous treatment with the three PPCPs gave alpha diversity values generally lower than those obtained for IBP and DCF, and higher than for TCS alone, but not significantly different from the controls, except for a higher evenness after 7 days.…”
Section: Bacterial Richness and Diversity In The Bps Microcosmsmentioning
confidence: 82%
“…Of these, there were 128 duplicates, and 16,013 were excluded on the basis of title and abstract screening. A total of 68 studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of ARGs reported are those that confer resistance to β-lactam antibiotics, aminoglycosides, fluoroquinolones and macrolides. However, of the studies, 12 (17.6%) did not have precise information on the types of ARGs found, as is the case for the reports made by Port et al [ 27 ], Han et al [ 48 ], Fang et al [ 51 ], Pan et al [ 54 ], Chen et al [ 55 ], Eduardo-Correia et al [ 57 ], Quintela-Baluja [ 42 ], Clarke et al [ 61 ], Fernandes Cardoso de Oliveira et al [ 62 ], Coutinho et al [ 45 ], Miranda et al [ 63 ], Lu et al [ 64 ], Jiang et al [ 65 ], and Qu et al [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations